Challenges in the Implementation of Aral Program as Perceived by the Teachers in Zone I Schools Division of Zambales - Joyce E. Atrero; Esmen M. Cabal (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Regional literacy gaps and poor international assessment scores prompted the Philippine government to establish the Academic Recovery and Accessible Learning (ARAL) Program under Republic Act 12028. This study investigated the challenges faced by teachers in implementing the ARAL Program in Zone 1, Schools Division of Zambales. Utilizing a descriptive quantitative survey design, data were gathered via purposive sampling from 129 public elementary school teachers across the districts of Sta. Cruz, Candelaria, and Masinloc. A self-developed 4-point Likert scale questionnaire assessed challenges across five structural domains. Teachers perceived the ARAL Program implementation as "Challenging" across all studied areas (overall weighted means: 3.00–3.08). Local Government Support emerged as the most severe challenge (M=3.08), heavily driven by difficulties in mobilizing local stakeholders (M=3.13). Access to Learning Materials (M=3.04) and Qualification of Tutors (M=3.04) presented equal difficulties, primarily due to poor internet connectivity obstructing digital resource access (M=3.15) and tutors lacking formal pedagogical training (M=3.13). Furthermore, student unwillingness to participate (M=3.13) and the burden of developing materials adaptive to both online and face-to-face setups (M=3.23) hindered effective student identification and delivery modes. Successful learning recovery is constrained by systemic hurdles, including weak community mobilization, digital infrastructure deficits, and untrained tutoring personnel. It is recommended that school divisions provide targeted multimodal material development training, invest in low-bandwidth or offline instructional alternatives, and forge formalized partnership agreements with local government units to secure sustained logistical and financial backing.